Colorimetric determination of peroxide value in vegetable oils using a paper based analytical device. (1st March 2023) - Ghohestani, Elham; Tashkhourian, Javad; Hemmateenejad, Bahram
Highlights: A simple and on-site paper-based analytical device for determine peroxide value. Needing low amount of samples, solvents, and reagents and does not need glassware and skilled personnel. A well-defined inverse logarithmic calibration curve is established between color intensity and PV. Abstract: Peroxide value (PV) is one of the most typically used quality parameters to monitor lipid oxidation. Here, a simple paper-based analytical device (PAD) has been developed to determine PV in vegetable oils. The analysis is based on setting up the iodometric titration, where hydroperoxides in the oil are reacted with excess iodide ions to generate iodine molecules, on the paper substrate. The device is composed of two paper layers acting as reaction and detection zones, aligned in a metallic mold. A well-defined inverse logarithmic calibration curve was established between the measured PV by the official iodometric method (ISO;3960, 2017) and the color intensity of PAD. It offered a working range of 0.01–30.0 meq/Kg. The limit of detection of 0.015 meq/Kg demonstrated enough sensitivity of the method to estimate peroxide value in edible oils. On-site and visual detection, low cost, simplicity, and less solvent consumption are advantages of the proposed device.